The influence of corporate social responsibility and customer satisfaction on customer loyalty at Bank Central Asia in Indonesia - Angelita, Ferawati; Andajani, Erna; Rahayu, Siti (Southeast Asian Journal of Service Management, 2024)
Corporate Social Responsibility (CSR) activities in Indonesia are currently increasing in various industries, including the hospitality industry. Bank BCA is one of the companies that carry out Corporate Social Responsibility (CSR) activities on the environment, economy, and society. This study aims to determine the effect of Corporate Social Responsibility (CSR) activities and customer satisfaction on customer loyalty at Bank Central Asia (BCA) Bank in Indonesia. This research is included in quantitative research and is included in causal research. This study has 3 variables including Corporate Social Responsibility (CSR) activities, customer satisfaction, and customer loyalty. This study uses a sample of 150 respondents who are customers of BCA Bank with a sampling technique that is non-probability sampling. The data obtained in this study will be processed with Structural Equation Modeling (SEM) techniques through SPSS and AMOS software. Based on the results of this study, shows that Corporate Social Responsibility (CSR) activities have a positive effect on customer satisfaction at BCA Bank, Corporate Social Responsibility (CSR) activities have a positive effect on customer loyalty at BCA Bank and customer satisfaction has positive effect on customer loyalty at BCA Bank.